2001
DOI: 10.2165/00128072-200103100-00002
|View full text |Cite
|
Sign up to set email alerts
|

School Refusal

Abstract: School refusal is differentiated from other attendance problems such as truancy and school withdrawal. It is characterised by the child's emotional upset at the prospect of going to school, parental awareness of and antipathy toward the problem, and an absence of significant antisocial behaviour in the child. The child's emotional upset is frequently associated with an anxiety disorder, but it may also be associated with a mood disorder. School refusal affects approximately 1% of school children across the pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(44 citation statements)
references
References 61 publications
2
42
0
Order By: Relevance
“…There are inconsistent study results in the literature. In some studies (Heyne et al, 2001;King & Bernstein, 2001), it is reported that school refusal is at equal rates in both genders; however, in another study (Nishida, Sugiyama, Aoki, & Kuroda, 2004), higher rates are shown for men. Based on the results, it can be stated that the roots of school refusal behaviours have more specific features, and cannot be completely explained through gender stereotypes.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…There are inconsistent study results in the literature. In some studies (Heyne et al, 2001;King & Bernstein, 2001), it is reported that school refusal is at equal rates in both genders; however, in another study (Nishida, Sugiyama, Aoki, & Kuroda, 2004), higher rates are shown for men. Based on the results, it can be stated that the roots of school refusal behaviours have more specific features, and cannot be completely explained through gender stereotypes.…”
Section: Discussionmentioning
confidence: 93%
“…Similarly, Maric, Heyne, MacKinnon, Widenfelt, and Westenberg (2012), claimed that negative automatic thoughts related aversion, and negative overgeneralizing cognitive distortion predict school refusal behaviour. For this reason, cognitive-behavioural techniques are mostly used techniques when studying on school refusal to define and alter school related irrational thoughts, and to reintegrate them into a specific school setting (Heyne, King, Tonge, & Cooper 2001;Kearney, 2008b).…”
Section: Introductionmentioning
confidence: 99%
“…The literature shows that school refusal is related to both internalizing disorders, such as anxiety, fatigue, somatic complaints and depression, and to externalizing disorders, such as verbal and physical aggression, and escape from school and/or home (Heyne, King, Tonge, & Cooper, 2001; Kearney, 2008). However, the role of some individual variables, such as personality and emotional skills, has been overlooked.…”
Section: Highlightsmentioning
confidence: 99%
“…One promising treatment, cognitive behavioral therapy [CBT], the most frequently reported approach in the literature, has been demonstrated to be e ective in remediating school refusal behavior and is o en used with multiple behavioral and cognitive techniques (e.g., Heyne et al, 2014;King, Tonge, Heyne, Turner, Pritchard, Young, Rollings, Myerson, & Ollendick, 2001). CBT is a short-term, focused approach that helps students e ectively manage their external and internal symptoms, modify their thoughts regarding schoolrelated events, and eventually integrate their thoughts on a particular adverse stimulus in school (Heyne, King, Tonge, & Cooper, 2001). Mansdorf and Lukens (1987) initially examined the e ectiveness of CBT in school refusal behavior with two school-age students.…”
Section: Introductionmentioning
confidence: 99%